2014
DOI: 10.1371/journal.pone.0112300
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1/Smad Signaling Pathway Regulates Epithelial-to-Mesenchymal Transition in Esophageal Squamous Cell Carcinoma: In Vitro and Clinical Analyses of Cell Lines and Nomadic Kazakh Patients from Northwest Xinjiang, China

Abstract: Invasion and metastasis are the major causes of death in patients with esophageal squamous cell carcinoma (ESCC). Epithelial-mesenchymal transition (EMT) is a critical step in tumor progression and transforming growth factor-β1 (TGF-β1) signaling has been shown to play an important role in EMT. In this study, we investigated how TGF-β1 signaling pathways contributed to EMT in three ESCC cell lines as well as 100 patients of nomadic ethnic Kazakhs residing in northwest Xinjiang Province of China. In vitro analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 18 publications
10
47
0
Order By: Relevance
“…Here, we demonstrated that TGF-β1 induces changes in the morphology of ESCC cells and their transition from epithelial to mesenchymal phenotype. This change was shown to be accompanied by the downregulation of E-cadherin and upregulation of vimentin expression, which is consistent with the data obtained in the previous studies 12,13…”
Section: Discussionsupporting
confidence: 92%
“…Here, we demonstrated that TGF-β1 induces changes in the morphology of ESCC cells and their transition from epithelial to mesenchymal phenotype. This change was shown to be accompanied by the downregulation of E-cadherin and upregulation of vimentin expression, which is consistent with the data obtained in the previous studies 12,13…”
Section: Discussionsupporting
confidence: 92%
“…phosphorylated Smad2/3 and Smad4 translocate to the nucleus, where they cooperate with transcription factors such as Snail and Twist to repress the expression of epithelial markers and activate the expression of mesenchymal markers. This signaling is referred to as TGF-β-activated Smad signaling in EMT [27][28][29]. Similar to previous studies, 2 ng/ml of TGF-β1 decreased expression of epithelial markers, increased expression of mesenchymal markers, which was accompanied by an increase in Smad2/3 activation (increased expression of phospho-Smad2/3) in HMrSV5 cells.…”
Section: Discussionsupporting
confidence: 79%
“…Distant metastasis is one of the main reasons for treatment failure in ESCC. EMT is a critical event in the progression toward cancer metastasis and many signaling pathways are involved in the regulation of EMT in ESCC, such as Akt/GSK‐3β/Snail, MAPK/ERK and TGF‐β1/Smad . Several studies have reported that the AKT/GSK‐3β signaling pathway is involved in the progression of EMT in human malignancies, such as gastric cancer, hepatocellular carcinoma and prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a critical event in the progression toward cancer metastasis and many signaling pathways are involved in the regulation of EMT in ESCC, such as Akt/GSK-3b/Snail, MAPK/ERK and TGF-b1/Smad. [25][26][27][28] Several studies have reported that the AKT/ Western blots comparing EYA4-knockdown and EYA4-overexpression cells with their respective control cells are seen in relative expression of (C) Akt, p-Akt-S473, GSK-3b, p-GSK-3b. b-actin was used as a loading control.…”
Section: Discussionmentioning
confidence: 99%